Use of a Wiki-Based Software to Manage Research Group Activities. - Ting Wang; Dmitri V. Vezenov; Brian Simboli (Issues in Science and Technology Librarianship)
This paper discusses use of the wiki software Confluence to organize research group activities and lab resources. Confluence can serve as an electronic lab notebook (ELN), as well as an information management and collaboration tool. The article provides a case study in how researchers can use wiki software in "home-grown" fashion to organize their research activities and how librarians can play a role in exploring or advocating wiki software for these purposes. Most of the focus in our discussion will be on ELNs, but we will also address other uses of Confluence. [ABSTRACT FROM AUTHOR]